The Influence of Pipe Geometry on the Critical Velocity of Horizontal Pneumatic Conveying of Coarse Particles. - Wirth, Karl-Ernst; Molerus, Otto (Powder Technology, 1985)
With single-phase flow a circular pipe cross-section is optimal, since the ratio of wetted perimeter to cross-sectional area is minimal. Similar arguments also hold good in the case of fully suspended solid loaded flow. Under those circumstances, however, in which in horizontal pipes more or less separation of flow occurs, i.e. in the case of strand flow, one may ask whether pipe profiles other than circular could be more suited. For circular and semicircular pipes with identical cross-sectional areas, theory and experiments yield critical velocities in the semicircular pipe which are about 25% smaller. © 1985.
UnivIS-Import:2015-03-05:Pub.1985.tech.ITC.mechve.theinf
Keywords: flow; fluidization; powder